POTRET BELAJAR MENGAJAR DI SEKOLAH: ADAPTASI KEBIASAAN BARU PEMBELAJARAN DI MASA PANDEMI COVID-19 - M. Arli Rusandi; Ledya Oktavia Liza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to determine the learning process during the adaptation of new habits during the Covid-19 pandemic in schools in Riau Province. This study uses a qualitative method with interview data collection techniques through the telephone network and the WhatsApp platform (chat and video call). The subjects of this study were 11 elementary school teachers, ten junior high school teachers and 20 high school teachers in Riau province who were selected randomly. Based on the results of the research that has been carried out, it can be concluded that the learning process during the new adaptation period during the Covid-19 pandemic that occurred in schools in Riau province mostly had in common; namely, the learning process was carried out in a mixed manner, namely offline and online, learning evaluation carried out by assigning tasks. The factors that hinder the learning process are the availability of applications, a less conducive atmosphere and less than optimal preparation.